PIG BASED WATER QUALITY ASSESSMENT IN EL-HAI RIVER BASIN, EL-KANTARA PLAIN, ALGERIA - Kerboub, D; Fehdi, C; El hmaidi, A; Azzi2, Y; Khemissi, C (university of eloued -جامعة الوادي, 2022)
Groundwater of the El-Kantara plain needs greater attention, because it is the alternative source of water for domestic and agricultural purposes. Water pollution affects both water quality and human health. Hence it is essential for continuous monitoring of the quality of groundwater so that pollution can be minimized. This study aims to evaluate the degree and extent of contamination of the Mio-Plio-Quaternary alluvial aquifer, in the El-Kantara area, Northern Biskra region (Algeria). A pollution index of groundwater (PIG) is proposed for quantification of water contamination at eleven (11) sampling different wells during four times at each well (dry period: September 2011/2014 and wet period February 2012/2015). PIG quantifies the status of concentrations of water quality measures with respect to their drinking water quality standards. The computed values of Pollution Index Groundwater (PIG) of El-Kantara aquifer in El-Hai River Basin vary from 0.746 (Insignificant pollution during wet period; February 2015) to 6.287(Very high pollution during dry period; September 2014). Spatial variation map has been prepared using GIS reveled that most of the study area accounts for very high pollution zones (61.36% of samples)
article
Keywords: Aquifer of El-Kantara; Drinking-water; Water quality standards; Hydrogeochimistry; El-Hai Basin River; Algeria